PENGARUH STRUKTUR ORGANISASI, ANALISIS JABATAN DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI DITJEN BIMAS BUDDHA KEMENTERIAN AGAMA RI DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING - ADHIKA VIRIYA DHIRO; ARIEF ALFIANDRY (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this study was to determine the effect of organizational structure, job analysis, and leadership style on work motivation and their impact on the performance of the employees of the Directorate General of Buddhist Guidance, Ministry of Religion of the Republic of Indonesia. The population in this study were employees of the Directorate General of Buddhist Guidance at the Ministry of Religion of the Republic of Indonesia. This study uses a probability sampling technique with a Puposive Sampling with a total of 84 samples. Data collection techniques through observation interviews and questionnaires with a Likert scale. Data were analyzed using WarpPLS (Partial Least Square) version 7.0. Based on the results of hypothesis testing, the results of this study indicate that organizational structure, job analysis, work motivation have an influence on employee performance and leadership style has no effect on employee performance.